2014
DOI: 10.3409/fb62_3.211
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP Analogue, dbcAMP, Affects Rabbit Ovarian Cell Proliferation, Apoptosis, Release of Steroids and Response to Hormones

Abstract: SIROTKIN A. V., BALAZI A., CHRENEK P. 2014. The cAMP analogue, dbcAMP, affects rabbit ovarian cell proliferation, apoptosis, release of steroids and response to hormones. Folia Biologica (Kraków) 62: 211-218.Cyclic adenosine monophosphate (cAMP)-related intracellular mechanisms can be important in the control of reproductive processes. The aim of the present study was to examine possible hormonal and intracellular mechanisms mediating the action of cAMP on ovarian cell functions, in particular the mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…These increases in cell proliferation and death suggest that bee pollen can promote ovarian cell turnover. Similar stimulatory actions on cultured ovarian cell turnover has been previously reported: promotion of both proliferation and apoptosis was observed in known regulators of ovarian functions such as follicle stimulating hormone (Sirotkin et al 2014(Sirotkin et al , 2017, leptin (Sirotkin et al 2012), IGF-I and ghrelin (Sirotkin et al 2014), some siRNAs controlling ovarian cell protein kinases (Sirotkin et al 2010), iron (Kolesarova et al 2011b), and the plant isoflavone daidzein (Sirotkin et al 2017) which is present in bee pollen (Denisow and Denisow-Pietrzyk 2016;Cornara et al 2017;Kieliszek et al 2018). Therefore, daidzein is one component that could be responsible for the effects of bee pollen on the ovary.…”
Section: Does Bee Pollen Directly Affect Ovarian Cell Viability?supporting
confidence: 83%
“…These increases in cell proliferation and death suggest that bee pollen can promote ovarian cell turnover. Similar stimulatory actions on cultured ovarian cell turnover has been previously reported: promotion of both proliferation and apoptosis was observed in known regulators of ovarian functions such as follicle stimulating hormone (Sirotkin et al 2014(Sirotkin et al , 2017, leptin (Sirotkin et al 2012), IGF-I and ghrelin (Sirotkin et al 2014), some siRNAs controlling ovarian cell protein kinases (Sirotkin et al 2010), iron (Kolesarova et al 2011b), and the plant isoflavone daidzein (Sirotkin et al 2017) which is present in bee pollen (Denisow and Denisow-Pietrzyk 2016;Cornara et al 2017;Kieliszek et al 2018). Therefore, daidzein is one component that could be responsible for the effects of bee pollen on the ovary.…”
Section: Does Bee Pollen Directly Affect Ovarian Cell Viability?supporting
confidence: 83%
“…As discussed earlier we and others have demonstrated that SIRT1 activation enhances cAMP levels [12,56,57]. Perhaps surprisingly, quite a few studies had linked elevated intracellular levels of cAMP to apoptosis in various cell types [77][78][79] including ovarian follicular cells and GCs [80][81][82][83]. For instance, it was shown that treatment of GCs with forskolin, or 8-bromo-cAMP induced apoptosis as evidenced by DNA fragmentation and chromatin condensation.…”
Section: Discussionmentioning
confidence: 88%
“…In the ovaries, cAMP is of utmost importance as a second messenger for growth and development of follicles in all stages [30][31][32]. Studies revealed that cAMP response element-binding protein 1 (creb1) and the cAMP analogue, dbcAMP were involved in the down-regulation of porcine and rabbit ovarian cell proliferation, respectively [33,34]. In addition, cAMP inhibited rat hepatocellular carcinoma cell proliferation and enhanced cell differentiation [35].…”
Section: Discussionmentioning
confidence: 99%